New Dimensions in Sociology: A Physico-Chemical Approach to Human Behavior by Mirza Arshad Ali Beg; Karachi: Hamdard Foundation Press, 1987. (American Journal of Islam and Society, 1989)
Let us start with the title of the book. Its first part is hardly exciting.Several sociology publications currently carry similar titles: New Horizonsin Sociology, New Directions in Sociology, New Debates in Sociology, ormerely New Sociology. It seems that most people writing about sociologythese days must write something new or not write at all.What is new about this book can be seen from the second part of itstille, A Physico-Chemical Approach 10 Human Behavior-eye-catching, evenstartling. There have been organic, evolutionary, and ecological analogiesused by sociologists in the past, often with great success. However, physicochemicalanalogy is something else. If, by using this title. Dr. Beg had inmind to shock sociologists into reading his book from cover to cover, hemust be congratulated, for, no doubt, the title is intriguing, to say the least.The contents do not reveal too much about the book. However, theymust not be taken lightly. Wi.lson (1975) produced yet another "new" and assertedthat human values, even customs and traditions, are genetically transmittedfrom one generation to another. Since then, he has won a number of adherentsto his point of view. So here it is: a physico-chemical approach to sociology.If Harvard publishes treatises like Wilson's Sociobiology, how can we rejectHamdard's New Dimensions as being out of hand? After all , Wilson is azoologist with hardly a flair for sociology in his dossier.The author of this book, Mirza Arshad Ali Beg, is a trained andexperienced chemist with graduate degrees from Karachi (MSc.) and BritishColumbia (Ph.D.). He began in 1941 as a senior research officer at the PakistanCouncil of Scientific and Industrial Research (PCSIR) and in 1985 becamethe director of its facilities in Karachi. Since then, he has been promotedto the secretarial rank in this organization. Dr. Beg has also held severalimportant posts in national and international organizations.Apparently, Dr. Beg is a qualified, experienced researcher in chemistry.As such, it is to his credit that in this book he has ventured far afield fromhis area of specialization. This book is a testimony to the fact that sociologyis not, has not been, and must not be the exclusive domain of sociologists.All throughout its relatively brief history, sociology has benefitted from thecontributions of historians, philosophers, psychologists, even engineers. Thus,if a chemist is trying his hand this time, we must not be too shocked ...